2015
DOI: 10.1371/journal.pone.0118170
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Characterization of Site-Directed Mutagenesis of Porcine Beta Defensin 2

Abstract: Porcine β defensin 2 (pBD2) is a small, cationic and amphiphilic antimicrobial peptide. It has broad antimicrobial activities against bacteria and plays an important role in host defense. In order to enhance its antimicrobial activity and better understand the effect of positively charged residues on its activity, we substituted eight amino acid residues with arginine or lysine respectively. All mutants were cloned and expressed in BL21 (DE3) plysS and the mutant proteins were then purified. These mutant versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Indeed, there may be no need for the giant panda to accumulate many nonsynonymous substitutions in its β-defensins for these to be different from their homologs in other carnivores. In some immune peptides, including β-defensins, a single amino acid substitution is sufficient to alter their molecular potency against pathogens 30 . Targeting a broad range of pathogens, Aime-DEFB139 may not need to change significantly under diversifying selection to cope with new pathogens, and an enhanced antimicrobial activity resulting from a point mutation could be sufficient for this coping ability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there may be no need for the giant panda to accumulate many nonsynonymous substitutions in its β-defensins for these to be different from their homologs in other carnivores. In some immune peptides, including β-defensins, a single amino acid substitution is sufficient to alter their molecular potency against pathogens 30 . Targeting a broad range of pathogens, Aime-DEFB139 may not need to change significantly under diversifying selection to cope with new pathogens, and an enhanced antimicrobial activity resulting from a point mutation could be sufficient for this coping ability.…”
Section: Discussionmentioning
confidence: 99%
“…β-defensins, the evolutionarily oldest defensins, consist of 30-45 residues of amino acid that includes 5-12 positively charged residues such as arginine and lysine. Typical structure of β defensins composed of an alpha helix with three beta sheets (Huang et al, 2015). The βdefensins are either constitutively expressed or induced in the skin and the mucosal surfaces of airways, digestive tract, and urogenital tract for inflammatory and infectious diseases (Elahi et al, 2006;Sang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These amino acids usually form highly defined cationic domains within the peptide structure (Hicks et al 2013, Lakshmaiah Narayana and. Increasing the charge of AMPs has been demonstrated to increase the antimicrobial activity in numerous studies (Bessalle et al 1992, Huang et al 2015. In parallel, it has also been shown that the elimination of peptide cationic charge drastically reduces antimicrobial activity (Schmidtchen et al 2014).…”
Section: Chargementioning
confidence: 99%
“…A systematic approach to mutagenesis is required to cover as much of the sequence space as possible. Previously, increasing the charge of antimicrobial peptides has been linked with increased antimicrobial activity (Huang et al 2015.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation